Morphological characters of Panicum maximum cv Gatton planted from different source of sapling - A., Fanindi; E, Sutedi (Indonesian Journal of Animal and Veterinary Sciences, 2014)
Morphological characters and agronomic information of Panicum maximum cv Gatton is required in forage crop breeding activities. Therefore a research was conducted to determine the morphology and characteristic of generative phase of Panicum maximum cv Gatton. The study was conducted in greenhouses, using a 40 cm diameter pot. The planting medium was soil from Ciawi (Latosol). Research design was Completely Randomized Design, with 10 replications. Treatments used were 2 types of planting material, 1) derived from the pols (vegetative) and 2 seeds. Plants used were Panicum maximum cv Gatton that have been collected and evaluated at the IRIAP, Ciawi. Variables measured were plant morphology, reproductive traits, seed production per panicle and seed quality. Results showes that morphological characters of cv Gatton derived from seed and pols was not significantly different (p > 0.05), whereas the flowering time and the time of seeds mature after cutting derived from the seeds was faster (p < 0.05) than cultivars derived from pols. While the production of seed derived from the seeds was higher (p < 0.05) when compared to that derived from the pols. Key Words: Morphological Characteristics, Seed, Pols, Panicum maximum